The Analysis of Dual-Junction Tandem Solar Cells Enhanced by Surface Dispensed Quantum Dots - Shun-Chieh Hsu; Yu-Ming Huang; Yu-Cheng Kao; Hao-Chung Kuo; Ray-Hua Horng; Chien-Chung Lin (IEEE Photonics Journal)
The luminescent down-shifting (LDS) effect of a colloidal quantum dot layer on a dual junction solar cell is explored and analyzed. A 5.47% enhancement of power conversion efficiency is recorded when green quantum dots are dispersed on device surface. The surface reflectance spectra before and after the quantum dot dispenses are necessary to decouple the different mechanisms between antireflective and LDS effects. A further deduction of formulation on the dual-junction device with antireflection and LDS effect is presented and as high as 44.6% of short-circuit current increase in the green quantum dot case can be attributed to the LDS effect according to our calculation.